(untitled) (Biomedicine & Healthcare Research, 2025)
We are pleased to present this new issue of Biomedicine & Healthcare Research, the official scientific journal of the Faculty of Medicine of Sousse. This volume features a selection of literature reviews, original research articles, case series, and case reports that reflect the journal’s aims and scope. This volume opens with a timely literature review by Aloulou et al., exploring the impact of gut microbiota dysbiosis on cancer-related cognitive impairment—a rapidly emerging field at the intersection of oncology, neurology, and microbiome science. Among the original contributions, Chaieb et al. investigate the prevalence and determinants of imposter syndrome among nurses, shedding light on an often-overlooked psychological burden among healthcare professionals. Meddeb et al. assess the impact of the COVID-19 pandemic on decision-making and diagnostic processes in non-COVID patients, offering valuable insights into systemic challenges during global health crises. El Omri et al. contribute two original articles: the first provides clinical and therapeutic insights into laryngeal papillomatosis, while the second presents a 20-year single-center experience in managing pediatric acute mastoiditis, highlighting evolving practices in otolaryngology. Other noteworthy contributions include: Athimni et al. on occupational exposures to formaldehyde and wood dust in nasopharyngeal carcinoma, A case series by Mseddi et al. on visceral artery aneurysms encountered in general surgery. A rare case reported by El Hadhri et al. of concurrent gastrointestinal stromal tumor and small bowel adenocarcinoma in a patient with neurofibromatosis type 1 We thank all contributors and reviewers for their commitment to scientific rigor. This volume reflects our shared goal: to advance evidence-based medicine through meaningful, regionally grounded research. We look forward to your continued readership and eagerly anticipate your future contributions to Biomedicine & Healthcare Research.